Metabolic effects of CCL5 deficiency in lean and obese mice - Zhou, Hui; Liao, Xiyan; Zeng, Qin; Zhang, Haowei; Song, Jianfeng; Hu, Wanyu; Sun, Xiaoxiao; Ding, Yujin; Wang, Dandan; Xiao, Yalun; Deng, Tuo (Frontiers in Immunology, 2023)
Accumulation and activation of immunocytes in adipose tissues are essential to obesity-induced inflammation and insulin resistance. Chemokines are pivotal for the recruitment of immunocytes in adipose tissue during obesity. Chemokine (C-C motif) ligand 5 (CCL5) plays a vital role in the recruitment of immunocytes to sites of inflammation. CCL5 expression level is increased in obese adipose tissue from humans and mice. However, the role of CCL5 in obesity-induced adipose inflammation remains unclear. Our study found that the CCL5 expression level was increased in the epididymal white adipose tissue (eWAT) of obese mice, particularly in CD8+ T cells. CCL5 knockout (KO) mice exhibited better glucose tolerance than wild-type (WT) mice under lean conditions. In contrast, CCL5 KO mice were more insulin resistant and had severe hepatic steatosis than WT mice under obese conditions. Increased T cells in adipose tissue heaven adipose inflammation in obese CCL5 KO mice. The compensatory increased T cell-associated chemokines may account for increased T cell content in the eWAT of obese CCL5 KO mice. These findings imply that CCL5 deficiency exacerbates adipose inflammation and impairs insulin sensitivity in the metabolic tissues of obese mice.